To make the equation \( x^2 - 18x + c = -80 + c \) into a perfect square trinomial, we first need to simplify it.
Let’s rewrite the equation as:
\[ x^2 - 18x + c + 80 - c = 0 \]
This simplifies to:
\[ x^2 - 18x + 80 = 0 \]
Now, we want to express \( x^2 - 18x + 80 \) as a perfect square. A quadratic in the form \( x^2 - bx \) can be turned into a perfect square by finding the needed constant.
To achieve the form \( (x - k)^2 \), where \( k \) is half of the coefficient of \( x \):
- The coefficient of \( x \) is \( -18 \), so half of that is \(-9\).
- To create a perfect square, we need to add \( (-9)^2 \) or \( 81 \).
Thus, we adjust \( c \) in our original equation to ensure that:
\[ x^2 - 18x + c = (x - 9)^2 \]
Here we set:
\[ c = 81 - 80 \]
So we need to balance this equation correctly:
If we require our trinomial to be a perfect square, it should actually be:
\[ x^2 - 18x + c - 80 = 0 \]
Now substituting \( c = 81 \):
\[ x^2 - 18x + 81 - 80 = 0 \ x^2 - 18x + 1 = (x - 9)^2 - 80 = 0 \ \]
This shows that for \( c = 81 \), the equation becomes \( (x - 9)^2 = 0\), confirming that it is a perfect square trinomial.
Thus, the value of \( c \) that makes the equation a perfect square trinomial is:
\[ \boxed{81} \]